Place-based policies and the housing market - Hans R.A. Koster; Jos van Ommeren (Tinbergen Institute, 2017)
We study the economic effects of place-based policies in the housing market taking into account search frictions. Theory indicates that beneficial policies increase house prices, but temporarily reduce sales times of owner-occupied properties. We investigate both effects for a place-based programme that improved public housing in 83 impoverished neighbourhoods throughout the Netherlands. We combine a first-difference approach with a fuzzy regression-discontinuity design to address the fundamental issue that these neighbourhoods are endogenously treated. Place-based policies increase house prices with 3.5 percent and, in line with theory, temporarily reduce sales times with 20 percent. The sales time effect dissipates within 7.5 years. The programme's welfare benefits to homeowners are sizeable and at least half of the value of investments in public housing.
Keywords: R30; R33; R38; 330; amenities; housing market; search frictions; house price; sales time; place-based policies